Competency in responding to infectious disease outbreaks among nurses in primary healthcare institutions: a quantitative, cross-sectional multicentre study - Zhu, Wei; Zhang, Jizhen; Yang, Liyao; Li, Jiping; Guo, Hongxia (Frontiers in Public Health, 2024)
Background Nurses’ competencies are crucial for infectious disease prevention and control. We aimed to investigate competencies in responding to infectious disease outbreaks of nurses in primary healthcare institutions and identify their training needs. Methods A cross-sectional study was conducted from June to September 2022, recruiting nurses from primary healthcare institutions across Sichuan Province. Their competencies and training needs were assessed using a modified Emergency Response Competency Scale for Infectious Diseases. Additionally, their sociodemographic characteristics and experience in infectious disease outbreak trainings were collected. Univariate analyses were used to compare competencies and training needs by participant characteristics. Multiple linear regression was conducted to identify determinants of their competencies. Results A total of 1,439 nurses from 44 primary healthcare institutions participated in this study. The overall competency and training needs had a median of 3.6 (IQR [3.1, 4.0]) and 4.0 (IQR [3.9, 4.7]), respectively. Age (β = −0.074, p = 0.005), experience in higher authority hospitals (β = 0.057, p = 0.035), infectious disease outbreak trainings attended within the last 5 years (β = 0.212, p < 0.001), and regions where the institutions located were determinants of the competencies. Conclusion The competencies in responding to infectious disease outbreaks among nurses in primary healthcare institutions were at a moderate level, influenced by varied factors.